KEPATUHAN MEDIKASI PENDERITA DIABETES MELLITUS TIPE 2 BERDASARKAN TEORI HEALTH BELIEF MODEL (HBM) DI WILAYAH KERJA PUSKESMAS MULYOREJO SURABAYA - Zahrotun Ulum; Kusnanto Kusnanto; Ika Yuni Widyawati (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Adherence play important role at therapeutic management of patients with type 2 Diabetes mellitus. The purpose this study was to identify and to analyse the factors associated with medication adherence.Methods: Design of the the study was descriptive analytic with cross-sectionalapproach. The population was patients with type 2 Diabetes mellitus in Puskesmas Mulyorejo Surabaya. Twenty eight as sample respondents were chosen by purposive sampling technique. The X variables in this study were age, sex, ethnicity, salary, knowledge, duration of illness, perceived susceptibility, perceived seriousness, perceived benefit, perceived barriers, self-efficacy, and family support. The Y variable was medication adherence of patients with type 2 Diabetes mellitus. Data were collected by using questionnaire and analyzed using chi square and spearman’s rho test with a degree of significance α<0.05.Result: Factors associated with medication adherence were sex, salary, knowledge, perceived seriousness, perceived benefit, self-efficacy, and family support. Factors not associated with mediacation adherence were age, ethnicity, duration of illness, perceived susceptibility, and perceived barriers. Perceived seriousness showed the strongest association with medication adherence (r=0.565).Discussion: Seven of twelve X variables were associated with perceived seriousness being the strongest association and five variables were not associated. It is expected that health care service develop the management of health service based on family and community to improve adherence at patients with type 2 Diabetes mellitus. Further research is suggested to enhance and develop the program to increase medication adherence.